Escaleras de madera wooden stairways David Fernandez Garvia, editor Hugo Quiroga Capovilla ; figrafi jucara Xavier de Sauza - GARCIA, David Fernandez; Capavilla, Hugo Quiroga; de Souza Jucara Xavier (Ediciones Faly s.l, 1999)
3 jilid ilus 30 cm